Mating disruption method against the vine mealybug, Planococcus ficus: effect of sequential treatment on infested vines. Issue 1 (21st September 2016) - Sharon, Rakefet; Zahavi, Tirtza; Sokolsky, Tamar; Sofer‐Arad, Carmit; Tomer, Maor; Kedoshim, Rika; Harari, Ally R.
Abstract: The vine mealybug, Planococcus ficus (Signoret) (Hemiptera: Pseudococcidae), is a major pest of vineyards. Here, we tested the efficacy of the mating disruption method against the pest when applied during one or two successive years in high and low infestation levels. Following 1 year of treatment, at low initial infestation levels a shutdown of pheromone traps was observed, along with a significant reduction in infested vines. With initially high infestation levels, a gradual reduction in infested vines was observed, with a trap shutdown seen only after the second year of pheromone application. We discuss the implications of the male mating disruption method for this pest in which the wingless females are aggregated with limited movement among vines, offering multiple mating opportunities for the flying male.